Patterns of Dietary Iron Intake, Iron Status, and Predictors of Haemoglobin Levels among Early Adolescents in a Rural Ghanaian District - Michael Akenteng Wiafe; Charles Apprey; Reginald Adjetey Annan (Journal of Nutrition and Metabolism)
Introduction. Early adolescents are vulnerable to anaemia due to lean body mass and menarche. The study assessed patterns of dietary iron intake, iron status, and predictors of anaemia among early adolescents. Method. One hundred and thirty-seven early adolescents were randomly selected in a rural district in Ghana. Multiple-pass 24-hour recall, iron food frequency questionnaire consisting of 27 food items, and semistructured questionnaire were administered. Variables include sociodemographics, dietary factors, and laboratory investigation including haemoglobin, ferritin, and C-reactive protein examination. Statistical Package for the Social Sciences (SPSS) software was used to calculate odds ratio and perform Mann–Whitney U test, chi-square (X2) test, exploratory factor analysis, and partial correlation (r) tests. Results. Participants had mean age of 11.5 years. Three iron dietary patterns explaining 28.7% of the total variance were identified: iron dietary pattern 1 (11%) composed of iron-rich, iron-enhancing, and iron-inhibiting foods; iron dietary pattern 2 (9.9%) comprised of iron-rich, iron-enhancing, and non-iron-inhibiting foods; and iron dietary pattern 3 (7.1%) consisting of stinging nettle, iron-inhibiting foods, non-iron-enhancing foods, non-cocoyam leaves, and non-turkey berries. Meal skipping (X2 = 5.7, p<0.05), times of eating a day (X2 = 12.6, p<0.05), and guardian educational status (X2 = 6.7, p<0.05) significantly affected dietary iron intake. Anaemia was associated with meal skipping (β = 0.367, p>0.05), snacking (β = 0.484, p>0.05), and junior high school (JHS) education (β = 0.544, p>0.05). Partial correlation showed statistically significant relationship between iron dietary pattern 1 and dietary iron (r = −0.234, p<0.01), iron dietary pattern 2 and dietary iron (r = -0.198, p<0.05), iron dietary pattern 2 and vitamin C (r = -0.201, p<0.05), and haemoglobin and ferritin (r = −0.178, p<0.05). Conclusion. Meal skipping, guardian educational status, and number of times of eating a day were significantly associated with dietary iron intake. Meal skipping, snacking, and adolescents with JHS education were positively associated with anaemia.